Neonatal Tetanus Case Series: A Tale of Survival and Tragedy at St Paul Hospital Millennium Medical College, Addis Ababa, Ethiopia - Bacha T; Abayneh M; Tefera DB (Dove Medical Press, 2024)
Tigist Bacha,1 Mahlet Abayneh,2 Dawit Bekele Tefera3 1Division of Pediatric Emergency and Critical Care, Department of Pediatrics and Child Health St Paul Hospital Millennium Medical College, Addis Ababa, Ethiopia; 2Division of Neonatology Department of Pediatrics and Child Health St Paul Hospital Millennium Medical College, Addis Ababa, Ethiopia; 3Ohio State Global One Health LLC, Addis Ababa, EthiopiaCorrespondence: Dawit Bekele Tefera, Tel +251-912360352, Email ddawitb@gmail.comBackground: Neonatal tetanus remains a significant threat in regions with limited healthcare access, despite being preventable through vaccination. The case-fatality rate of untreated neonatal tetanus is close to 100%. Even one case of neonatal tetanus regarded as a failure of the healthcare system, making it essential to remain mindful of this disease's relevance to public health. Two cases of neonatal tetanus are presented, highlighting the severe consequences of the disease. One infant survived after ICU treatment, while the other succumbed despite medical intervention.Conclusion: These cases underscore the critical need for clean delivery practices and Tetanus anti-toxoid vaccination for women of reproductive age. Improving access to quality antenatal healthcare and promoting clean birth practices are essential in reducing the incidence of neonatal tetanus and preventing unnecessary deaths.Keywords: neonatal tetanus, home delivery, Ethiopia